Genome-wide characterization of nascent RNA processing in plants. (October 2022) - Qin, Yuwei; Long, Yanping; Zhai, Jixian
Abstract: Following transcription initiation, RNA polymerase II (Pol II) elongates through the genic region and terminates after the polyadenylation signal. This process is accompanied by splicing, 3′ cleavage, and polyadenylation, to eventually form a mature mRNA. Recent advances in short-read and long-read high-throughput sequencing methods have shed light on the global landscape of these co-transcriptional events at nucleotide resolution. In this mini review, we summarize recent developments in genome-wide approaches that broadened our understanding of nascent RNA processing in plants.